Experimental Study of Environment Friendly Mixed Refrigerant to Replace R-134a in a VCR System with Testing and Training of ANN - Austin, N.; Rajeev, D.; Merinto, P.Anto Paulin; Manoj, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This work presents an experimental study on environment friendly mixed refrigerant to replace R134a in vapour compression refrigeration (VCR) System. The mixed refrigerants investigated are propane (R290), butane (R600), isobutene (R600a) and R134a. Even though the ozone depletion potentials of R134a relative to CFC-11 are very low; the global warming potentials are extremely high and also expensive. For this reason, the production and use of R134a will be terminated in the near future. Hydrocarbons are free from ozone depletion potential and have negligible global warming potential. The results showed that, mixed refrigerant with charge of 80 g satisfy the required freezer air temperature, when R134a with a charge of 110 g is used as refrigerant. The actual COP of refrigerator using mixed refrigerant was almost nearer that of the system using R134a as refrigerant. The coefficient of performance of the vapour compression refrigeration system using mixed refrigerant MR-3 [R134a/R290/ R600a/ R600 (20/35/40/5)] is having very close value with R134a and the Global warming potential of MR-3 is negligible when compared with R134a. Â Hence the mixed refrigerant MR-3 is chosen as an environmental friendly alternate refrigerant to R134a. Also the back propagation algorithm is implemented for training artificial neural network (ANN) to find out the optimum mixture having higher COP.Â 